KEWENANGAN BADAN MUSYAWARAH (BAMUS) NAGARI DALAM PENYELENGGARAAN PEMERINTAHAN NAGARI DI KABUPATEN AGAM - Prahara, Surya (e-Journal Pelangi volume 6 No.1, 2013)
The function of BAMUS is to receive peopleâs aspiration and to be Wali Nagariâs companion in administering Nagari. BAMUS and Wali Nagari are Nagariâs officials who are able to guide and prosper Nagariâs people. Institute of Nagariâs government is stated on Peraturan Daerah Kabuten Agam number 12, 2007 which is about Nagariâs government. PERDA must regulate the organizing of Nagari, in contrary it produces some overlapping interests between BAMUS and Wali Nagari. This problem directs the researcher to conduct a research about the authority of BAMUS in administering Nagari at Kabupaten Agam. The finding of this research prove that it is rarely for BAMUS to corporate with Wali Nagari in organizing the governmence. It is happen because a conflict which is shown that both BAMUS and Wali Nagari fell that they have same opportunity in deciding systems and programs for Nagari.